Initial management of a pregnant woman with trauma - Richa Aggarwal; Kapil Dev Soni; Anjan Trikha (Wolters Kluwer Medknow Publications, 2018)
Trauma is a leading nonobstetric cause of mortality among pregnant women. Managing a pregnant trauma victim is a unique challenge as one is dealing with two lives at the same time. Initial optimal management of a parturient plays an important role in survival. Various physiological and anatomical changes occur in pregnancy that has important implications in the management. Some complications like abruption placenta, rupture uterus, amniotic fluid embolism and isoimmunization are peculiar to pregnant trauma patients. In this review, we discuss the initial management of parturient with trauma along with various physiological and anatomical changes and their implications.